Capital vs. Digital Labor in the Post-industrial Information Age: A Marxist Analysis. (May 2020) - Kumar, T.; Jena, Lalatendu Kesari
Abstract: In the third millennium AD, humanity has reached the phase of the post-industrial information age. This age is characterized by the ubiquitous usage of Information and Communication Technologies (ICTs) in all aspects of social reality. ICTs are not just a tool for automation of social production but are qualitatively different from other preceding technologies. It can be understood that ICTs are situated at the cutting edge of current global capitalism. There is a danger that ICTs are enhancing capitalist consumerism by converting the "complete human being" into the "complete consumer." ICT-enabled "telework" has changed the "political economy of the home, " so that more surplus value can be extracted. ICTs have influenced the contestation of time between capital and labor that has been happening all through the history of capitalism. "Telework" and flexible production have influenced workers' powers of collective bargaining. There are new challenges in organizing workers in the gig economy. When the ontological roots of ICTs are situated within the neo-Marxist Habermasian framework of critical theory, its potential for human emancipation is understood. On the contrary, there is also a danger that ICTs may end up as a tool to consolidate and strengthen the existing powers of the bourgeoisie. After engaging with such issues, this article surmises that the nature of the relation between capital and labor in the post-industrial information age is qualitatively different from the earlier industrial age. Nevertheless, it concludes that the possibilities of labor getting into a more just relation with capital and in the process bring about a more equitable global social order still exists.